IMPLEMENTASI KEBIJAKAN PERAN KOMITE SEKOLAH SMK NEGERI 5 SAMARINDA (REALISASI KEMENDIKNAS NOMOR 044/U/2002 TENTANG DEWAN PENDIDIKAN DAN KOMITE SEKOLAH) - A. Amirunsyah Awie (Jurnal Paradigma (JP), 2017)
The existence of the school committee as been arranged in National Education Minister Decision Number 044/U/2002 formed in order to organize society’s aspiration, to develop society’s role, and to create democratics situation to implement the education so that educational high quality can be reached. The development of educational high quality at school need to be supported by headmasters’ managerial ability. School must be progressed every year. Therefore, good relationship among teachers must be created so that there will be a more condusive and cozier working climate and condition. Thus, the arrangement of physical appearance and school management must be built so that school can be an educational environment which can grow creativity and discipline to increase educational high quality.